The effect of caffeine ingestion on human neutrophil oxidative burst responses following time-trial cycling - Walker, G. J.; Dziubak, A.; Houghton, L.; Prendergast, C.; Lim, L.; Bishop, N. C. (Journal of Sports Sciences, 2008)
Following fixed-duration exercise of submaximal intensity, caffeine ingestion is associated with an attenuation of the exercise-induced decline in N-formyl-methionyl-phenyl-alanine (f-MLP) stimulated neutrophil oxidative burst. However, the response following high-intensity exhaustive exercise is unknown. Nine endurance-trained male cyclists ingested 6 mg caffeine or placebo per kilogram of body mass 60 min before cycling for 90 min at 70% of maximal oxygen consumption ([Vdot]O2max) and then performing a time-trial requiring an energy expenditure equivalent to 30 min cycling at 70% maximum power output. Time-trial performance was 4% faster in the caffeine than in the placebo trial (P = 0.043). Caffeine was associated with an increased plasma adrenaline concentration after 90 min of exercise (P = 0.046) and immediately after the time-trial (P = 0.02). Caffeine was also associated with an increased serum caffeine concentration (P < 0.01) after 90 min of exercise and immediately after the time-trial, as well as 1 h after the time-trial. However, the f-MLP-stimulated neutrophil oxidative burst response fell after exercise in both trials (P = 0.002). There was no effect of caffeine on circulating leukocyte or neutrophil counts, but the lymphocyte count was significantly lower on caffeine (20%) after the time-trial (P = 0.003). Our results suggest that high-intensity exhaustive exercise negates the attenuation of the exercise-induced decrease in neutrophil oxidative burst responses previously observed when caffeine is ingested before exercise of fixed duration and intensity. This may be associated with the greater increase in adrenaline concentration observed in the present study.